Dampak Kecanduan Game Online Mobile Legends terhadap Tingkat Emosional Siswa SMA - Lidya Rahmawati; Desy Safitri; Sujarwo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Abstract Nowadays, smartphones are not only used for work, but rather as entertainment for children and teenagers, for example online games. The existence of online games has a big impact on teenagers. If you cannot control yourself, you can lose track of time and forget other activities. If online games are overused, it will have detrimental effects. on teenagers’ emotional development. This research aims to analyze the consequence of Mobile Legends addiction to online games on the emotional level of high school students. A literature study was the research methodology employed in this study. Documentation of pertinent journals was the method of data collection employed. Based on the research findings, there appears to be an addictive influence due to playing Mobile Legends the emotional impact of online games of high school students. High school students who are still teenagers have unstable emotions. Addiction to video games can be harmful to students’ emotional levels, namely students become irritable, speak harshly, get easily stressed, anxious and aggressive. Parental war is very important to shield kids from developing a gaming addiction.